2019
DOI: 10.1101/871012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AUTS2 regulation of synapses for proper synaptic inputs and social communication

Abstract: Impairments in synapse development are thought to cause numerous psychiatric disorders.Autism susceptibility candidate 2 (AUTS2) gene has been associated with various psychiatric disorders, such as autism and intellectual disabilities. Although roles for AUTS2 in neuronal migration and neuritogenesis have been reported, its involvement in synapse regulation remains unclear. In this study, we found that excitatory synapses were specifically increased in the Auts2-deficient primary cultured neurons as well as Au… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…A similar phenotype was observed in Auts2 cKO cerebellum; dendritic spine numbers as well as excitatory inputs were increased without affecting inhibitory inputs in PCs. Because most of the dendritic spines and excitatory inputs we observed should correspond to PF synapses, AUTS2 may also function to restrict the number of PF synapses via its action in the cell nuclei, as was reported for the telencephalon (Hori et al, 2019).…”
Section: Cacna1asupporting
confidence: 56%
See 1 more Smart Citation
“…A similar phenotype was observed in Auts2 cKO cerebellum; dendritic spine numbers as well as excitatory inputs were increased without affecting inhibitory inputs in PCs. Because most of the dendritic spines and excitatory inputs we observed should correspond to PF synapses, AUTS2 may also function to restrict the number of PF synapses via its action in the cell nuclei, as was reported for the telencephalon (Hori et al, 2019).…”
Section: Cacna1asupporting
confidence: 56%
“…Consistent with this, downregulation of Auts2 in PCs leads to the enhancement of PF-dependent excitatory neurotransmission. We previously showed that AUTS2 restricts the number of excitatory synapses without affecting that of inhibitory synapses in the telencephalon (Hori et al, 2019). This function is elicited by nuclear AUTS2, because nuclear-localizing but not cytoplasmic-localizing AUTS2 is able to rescue the excessive spine phenotype in cultured hippocampal neurons from Auts2 mutant mice.…”
Section: Cacna1amentioning
confidence: 98%
“…To obtain a deeper understanding, we first took a conventional approach by categorizing all syllables into twelve types ( Fig. 2C ) based on their spectrotemporal patterns, according to previous reports (Hori et al, 2020; Kikusui et al, 2011; Scattoni et al, 2008). The USV acoustic features of the twelve syllable types are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Primary hippocampal cultures were prepared as previously described (Hori et al., 2020) with some modifications. 12 mm glasses were coated with 0.1 mg/ml PDL (Sigma‐Aldrich) a day before seeding.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that mutations in important genes for nervous system development cause a variety of NDDs. For example, autism susceptibility candidate 2 ( AUTS2 ) participates in neuronal differentiation and migration, neurite extension and synaptogenesis, but mutations in that gene cause a wide spectrum of disorders, such as schizophrenia, depression, ASD, ADHD, ID/DD and language disability (Hori & Hoshino, 2017; Hori et al., 2014, 2020). Given that DSCAML1 is also involved in various steps in the nervous system development, we suspected that mutations in DSCAML1 may be related not only to epilepsy but also other NDDs.…”
Section: Introductionmentioning
confidence: 99%